Cohesion in Spanish as a Second Language in an Indigenous School (2019)
This qualitative action research study analyzed the effect of Task Based Learning (TBL) through meaningful materials in the writing process of Spanish as a Second Language (SSL) for fifth graders from a Sikuani indigenous school located in Puerto Gaitán, Meta, Colombia. Throughout the sessions, task included different materials and games, such as a linguistic roulette, in order to help students foster cohesion when writing in Spanish as a second language. The instruments used to collect data were students’ artifacts (narrative texts), field notes, and semi-structured interviews. The results obtained showed that after the implementation, students were able to write short sentences using the parts of speech, such us articles, nouns, nd verb conjugations, accurately according to Spanish grammar.